(untitled) (Bangladesh Journal of Physics, 2025)
High energy linear accelerators are being used for treatment of cancer patients. In radiotherapy, the peripheral doses also attack the normal and healthy cells. According to the suggestion of LNT model, the issue of peripheral dose cannot be neglected. This study investigated the outfield photon beam skin dose in radiotherapy of Elekta medical Linac operated at 15 MV operational voltage using MTS-7 TL crystal. Before Linac exposure, TLDs were calibrated using 137Cs source. Then, TLDs were inserted on the phantom surface for Linac exposure. This study found that the photon skin dose increases with the increase of delivered dose and field size. As a function of the delivered dose, the highest doses were found 181.65 mSv and 78.39 mSv for delivered dose 300 cGy with field size 10 × 10 cm2 for Linac-1 and Linac-2 respectively. While, investigating the field dependency, the highest dose was found 511.30 mSv for field size 20 × 20 cm2 for 200 cGy delivered dose (Linac-1). According to the LNT model, this undesired radiation exposure may arise the risk of second cancer which makes this study extremely mandatory. Bangladesh Journal of Physics, Vol. 32, Issue 1, pp. 13 – 19, June 2025